2012
DOI: 10.3109/09593985.2012.714445
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic rhinosinusitis using erythromycin phonophoresis

Abstract: Bacterial biofilms have been implicated in many chronic infective diseases, including chronic rhinosinusitis (CRS). Therapeutic ultrasound enhances the breakdown of bacterial biofilms and is clinically effective in CRS treatment, while phonophoresis has also been utilized for antibiotic delivery through the skin. The objective of this case report is to describe the results of a novel treatment, erythromycin phonophoresis, in a woman with CRS. A 31-year-old woman with a 7-month history of CRS refractory to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It has previously been reported that therapeutic US in either continuous or pulsed mode is effective in treating symptoms of patients with acute rhinosinusitis (Høsøien, Lund, and Vasseljen, 2010) or CRS (Ansari, Fathali, Naghdi, and Hasson, 2010;Ansari, Naghdi, Farhadi, and Jalaie, 2007;Ansari et al, 2012;Ansari et al, 2013;Naghdi, Ansari, and Farhadi, 2008;Nakhostin Ansari, Naghdi, and Farhadi, 2004;Rocha et al, 2011;Young, Morton, and Bartley, 2010). Overall, the results found in this study agree with prior reports.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…It has previously been reported that therapeutic US in either continuous or pulsed mode is effective in treating symptoms of patients with acute rhinosinusitis (Høsøien, Lund, and Vasseljen, 2010) or CRS (Ansari, Fathali, Naghdi, and Hasson, 2010;Ansari, Naghdi, Farhadi, and Jalaie, 2007;Ansari et al, 2012;Ansari et al, 2013;Naghdi, Ansari, and Farhadi, 2008;Nakhostin Ansari, Naghdi, and Farhadi, 2004;Rocha et al, 2011;Young, Morton, and Bartley, 2010). Overall, the results found in this study agree with prior reports.…”
Section: Discussionsupporting
confidence: 95%
“…The OMC was scored as 0 or 3 (not occluded or occluded). The individual sinus scores were added to obtain the total CT score for each side (0 ¼ clear to 18 ¼ total opacification) (Ansari, Fathali, Naghdi, and Hasson, 2010;Ansari et al, 2012;Ansari et al, 2013). The total CT score for each patient was obtained by adding the right and left CT scores ranging from 0 ¼ clear to 36 ¼ total opacification.…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations